Back Cover. (31st October 2022) - Unknown
Abstract : The cover image is based on the Original Article Lymphatic microcirculation profile in the progression of hypertension in spontaneously hypertensive rats by Bing Wang et al., https://doi.org/10.1111/micc.12724 .